2009
DOI: 10.1007/s10882-009-9172-6
|View full text |Cite
|
Sign up to set email alerts
|

Educational Priorities for Children with Cri-Du-Chat Syndrome

Abstract: There are few data on the educational needs of children with cri-du-chat syndrome: a neurodevelopmental disorder that affects learning and development. We therefore designed an Internet survey to identify parents’ educational priorities in relation to children’s level of need/ability. The survey listed 54 skills/behaviors (e.g., toileting, expresses wants and needs, and tantrums) representing 10 adaptive behavior domains (e.g., self-care, communication, and problem behavior). Parents rated their child’s curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Although this questionnaire had been used in three different studies and its construct validity had been confirmed (Pituch, Green, Didden, Whittle et al, 2010;Pituch, Green, Didden, Lang et al, 2010;Pituch et al, 2011), when a questionnaire is used in research it is recommended to implement Factor Analysis (FA) to extract the underlying latent variables (Howitt & Cramer, 2011). This was done for both Part A and Part B.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…Although this questionnaire had been used in three different studies and its construct validity had been confirmed (Pituch, Green, Didden, Whittle et al, 2010;Pituch, Green, Didden, Lang et al, 2010;Pituch et al, 2011), when a questionnaire is used in research it is recommended to implement Factor Analysis (FA) to extract the underlying latent variables (Howitt & Cramer, 2011). This was done for both Part A and Part B.…”
Section: Data Analysis Proceduresmentioning
confidence: 99%
“…The educational needs of children with CdC, according to their parents' opinions, have been discussed by Pituch et al [15], who reported parents with high priority personal safety skills.…”
Section: Discussionmentioning
confidence: 99%
“…Although the constellation of symptoms was described in multiple studies from the 1970s to the late 1990s, research over the past 20 years suggests greater phenotype variability as identified by significant advances in molecular genetic techniques. Specifically, the use of sophisticated methods has enabled researchers to better determine cognitive, learning, social, emotional, and behavioral outcomes of cri du chat syndrome and other genetic disorders (Cornish & Bramble, 2002;Pituch et al, 2010). Given the variability in deletion size and type, identifying phenotypic subsets is informative for both diagnosis and prognosis (Cerruti Mainardi, 2006).…”
Section: Etiologymentioning
confidence: 99%
“…It has been suggested that individualized education program goals should reflect parent priorities for the child's learning and development. Pituch et al (2010) surveyed parents of children with cri du chat syndrome to identify the educational priorities that parents have for their children. With respect to high-priority skills rated by the parents, communication was deemed important, particularly listening and responding appropriately to the teacher, asking for information when needed, and following directions.…”
Section: Cognitive/academicmentioning
confidence: 99%
See 1 more Smart Citation